Consumer behavior to Thai fruit consumption during COVID-19 pandemic in Jakarta, Indonesia - Somsak Vivithkeyoonvong; Shasa Chairunnisa; Kijsart Onngernthayakorn; Jedsadaporn Sathapatyanon (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Indonesia imports fruits from around the world to serve people’s demand. Thailand as one of the fruit exporters to Indonesia needs to further explore what influences the consumption of Thai Fruits in Indonesia. Moreover, currently the COVID-19 pandemic likely affects all sectors, including the agriculture sector. This study aims to analyze the relation between socioeconomic characteristics and consumer behavior, particularly the pandemic period, that affects the purchasing decision of Thai Fruits. Using a structured questionnaire, random sampling of 1,736 respondents who shop at 5 All Fresh Supermarket branches were interviewed. The data was analyzed using the chi square test and binary logistic regression. The results found that socioeconomic characteristics such as age, gender, education, occupation, and income had a relation with Thai Fruits purchasing decision. In term of product awareness for instance, quality and taste is the utmost concern for customers. However, during COVID-19 pandemic, the level of customers’ consideration for quality and safety is clearly higher. Therefore, a different strategy is needed to convince consumers. The result also found that tasting experience influences purchasing decision significantly. To enhance international economic development, such agricultural products must respond to the customers’ needs and mutual cooperation between trading countries.JEL Classification:  F13; Q13; Q17